Non-typhoidal Salmonella among slaughterhouse workers and in the pork value chain in Uganda - Kivali, Velma; Roesel, Kristina; Dohoo, I.; Alinaitwe, Lordrick; Bugeza, James K.; Hoona, J.J.; Mugizi, Denis R.; Kankya, C.; Sinh Dang-Xuan; Szabo, I.; Rösler, U.; Friese, A.; et al. (International Livestock Research Institute, 2024)
Key messages Bacteria such as non-typhoidal Salmonella can be transmitted through cross-contamination in the pork value chain. Improving hygiene and pork handling practices at slaughterhouses and retail points is essential to ensure food safety. Slaughterhouses could be used for sentinel surveillance of zoonotic infections in humans and animals.